AI-DRIVEN ECO-TOURISM RECOMMENDATION SYSTEMS: AN EMPIRICAL INVESTIGATION OF IMPLEMENTATION SUCCESS FACTORS IN IRAQ - Rasha Talib Ahmed Alnaqeeb; Muthana Faaeq Almasoodi; Sura Abdullateef Hadi Alshammari; Ansam Ghanayem (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study aims to develop and evaluate an AI-powered recommendation system for sustainable eco-tourism in Iraq, addressing the critical need for environmentally conscious travel solutions in a region with rich cultural heritage and diverse ecosystems. Through quantitative analysis of data collected from 398 tourism sector professionals, the research examines the integration of artificial intelligence in promoting sustainable tourism practices. The findings reveal significant success in system implementation, with accuracy rates of 85-95% and strong correlations between technical-environmental (0.88) and environmental-economic (0.85) components, demonstrating the viability of AI-driven solutions in balancing ecological preservation with economic development. The study contributes to both theory and practice by providing a comprehensive framework for implementing AI-powered eco-tourism systems in developing regions, while offering empirical evidence of the effectiveness of digital technologies in promoting sustainable travel practices. These insights have important implications for policymakers and tourism stakeholders seeking to leverage technological innovation for sustainable tourism development.